Effect of practice exergames on the mood states and self-esteem of elementary school boys and girls during physical education classes: A cluster-randomized controlled natural experiment - Mayron da Cruz W.* (2020)
© 2020 Andrade et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.Reduced physical exercise can impact children’s mental health. Use of active electronic games can help promote psychological health. Physical education (PE class) uses different resources, methods, and contents to promote student health. We investigated the effect of exergames on the mood and self-esteem of children and compare it that of with traditional PE classes. From a sample of 213 children (7–11 years old), 140 from 10 classes of the fourth and fifth grades of elementary school (59 boys, 81 girls; mean age 9.41±0.48 years), allocated to an experimental group (EG; n = 68; five clusters) and a PE group (PE; n = 72; five clusters), participated in this experimental controlled study. The EG practiced exergames during three 40-minute classes, and the PE group held three routine curricular PE classes. Brunel’s Mood Scale and Rosenberg’s Self-Esteem Scale were applied. Repeated measures ANOVA identified differences between sexes and groups. The main results of the EG demonstrated reduced tension in girls (p <0.05; ES: 0.62; 95% CI: 0.17–1.05). Regarding sex comparisons, anger was lower in girls (F: 4.57; p <0.05; ES: 0.61; 95% CI: 0.11–1.11) in the EG. Vigor was higher in girls in the EG than in those in the PE group (F: 5.46; p <0.05; ES: 0.56; 95% CI: 0.12–1.01). The main results of the PE group indicated increased self-esteem in boys (p <0.05; ES: 0.58; 95% CI: 0.08–1.07) and reduction of girls’ mental confusion (p <0.05; ES 0.58; 95% CI 0.15–1.06). Thus, exergames impact boys’ and girls’ self-esteem and mood, as well as traditional physical education classes. Further study on exergames in schools is essential, with long-term effects on physical and mental health. Exergames bring interesting, varied content, technology, and innovation that can increase the attractiveness of physical education.